2007
DOI: 10.1186/1475-2875-6-90
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with Trypanosoma cruzi protects mice against early death by neurological or pulmonary disorders induced by Plasmodium berghei ANKA

Abstract: Objective: The objective of this study was to investigate whether the infection of C57BL/6 mice by P. berghei ANKA, which causes severe malaria, was modulated by co-infection with Trypanosoma cruzi. Methods:Groups of C57BL/6 mice were infected either with P. berghei ANKA, T. cruzi strain G, or with both parasites. The presence of parasites was checked by microscopic examination of blood samples. Symptoms of neurological or respiratory disorders, as well as mortality, were registered. Breakdown of the blood bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…It is also well documented that the complex formed by EB and albumin is excluded from the brain parenchyma by a fully functional BBB, so brain tissue from uninfected controls would have remained unstained by EB (Okamura et al, 2010; Marchi et al, 2010). This has been a consistent observation in a number of studies in which EB was used to evaluate the integrity of the BBB in experimental settings, such as Plasmodium infections in mice (Egima et al, 2007) and ultrasound-induced vascular disruption in rats (Wei et al, 2013). In the case of NCC, involvement of the BBB has been reported in the murine model by demonstrating migration of leukocytes in the brain of mice experimentally infected with Mesocestoides corti (Alvarez and Teale, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…It is also well documented that the complex formed by EB and albumin is excluded from the brain parenchyma by a fully functional BBB, so brain tissue from uninfected controls would have remained unstained by EB (Okamura et al, 2010; Marchi et al, 2010). This has been a consistent observation in a number of studies in which EB was used to evaluate the integrity of the BBB in experimental settings, such as Plasmodium infections in mice (Egima et al, 2007) and ultrasound-induced vascular disruption in rats (Wei et al, 2013). In the case of NCC, involvement of the BBB has been reported in the murine model by demonstrating migration of leukocytes in the brain of mice experimentally infected with Mesocestoides corti (Alvarez and Teale, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…It decreases the risk of severe malaria disease albeit increases the chances for clinical malaria early in the infection. A similar phenomenon was observed in murine co-infections with Trypanosoma cruz i and P. berghei ANKA, where the acute symptoms and pathological signs of ECM were absent [55] . There is a lack of data regarding Plasmodium and acute bacterial infection pathology.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have demonstrated that the course of a Plasmodium infection can be influenced by the presence of a second pathogen in the same host, either by aggravating malaria-associated pathology [21, 42], or by conferring protection against disease severity [43, 44]. However, despite the geographical overlap between the etiological agents of sleeping sickness and malaria, whether an ongoing infection by T .…”
Section: Discussionmentioning
confidence: 99%
“…cruzi and P . berghei do not develop ECM symptoms, presumably due to a reduction in the accumulation of CD8 + T cells in the brain of those animals [44]. Therefore, during a T .…”
Section: Discussionmentioning
confidence: 99%